Morphological, physical, and mechanical properties of sugar-palm (Arenga pinnata (Wurmb)Merr.)- reinforced silicone rubber biocomposites - Kamarul Bahrain, Siti Humairah; Nik Masdek, Nik Rozlin; Mahmud, Jamaluddin; Mohammed, M. N.; Salit, Mohd Sapuan; Ilyas, R. A.; Mohamed, Abdullah; Shamseldin, Mohamed A.; Abdelrahman, Anas; Asyraf, M. R. M. (Multidisciplinary Digital Publishing Institute, 2022)
The development of environmentally benign silicone composites from sugar palm fibre and silicone rubber was carried out in this study. The mechanical, physical, and morphological properties of the composites with sugar palm (SP) filler contents ranging from 0% to 16% by weight (wt%) were investigated. Based on the uniaxial tensile tests, it was found that the increment in filler content led to higher stiffness. Via dynamic mechanical analysis (DMA), the viscoelastic properties of the silicone biocomposite showed that the storage modulus and loss modulus increased with the increment in filler content. The physical properties also revealed that the density and moisture absorption rate increased as the filler content increased. Inversely, the swelling effect of the highest filler content (16 wt%) revealed that its swelling ratio possessed the lowest rate as compared to the lower filler addition and pure silicone rubber. The morphological analysis via scanning electron microscopy (SEM) showed that the sugar palm filler was evenly dispersed and no agglomeration could be seen. Thus, it can be concluded that the addition of sugar palm filler enhanced the stiffness property of silicone rubber. These new findings could contribute positively to the employment of natural fibres as reinforcements for greener biocomposite materials.